Evaluation of CT Scan Findings In Patients Presenting With Headache - Nepal, Pankaj; Shrestha, A; Ghimire, N (Journal of Chitwan Medical College, 2014)
Headache is one of the most common medical complaint however, the secondary causes of headache are unusual. Neuroimaging in headache is both expensive and has a low yield. Most patients with intracranial pathology have alarming clinical features raising “ red flag” signs. Thus appropriate selection of patients with headache for neuroimaging to look for secondary cause is important. Red flags act as screening tool to help in identifying those who get benefit from neuroimaging. These steps not only increase yield, but also limit cost as well as burden in health care system. The aim of our study was to evaluate all the CT scan findings in patients presenting with headache in Chitwan Medical College who underwent CT scan of head from February 2013 to September 2013 for period of seven months. Prospective observational study was performed in 256 patients, who underwent CT scan of head in this duration. Out of 256 patients, only 26 patients (10.1%) showed some form of brain parenchymal pathology. Other associated findings were sinusitis in 28 (11%), bone related in 10 (3.9%), and mastoiditis in 6 (2.3%) patients. The most prevalent pathology found was sinusitis, which was located in the maxillary sinus. The findings were significant in headache associated with other neurological findings, 16 out of 24 patients (67%) as compared to chronic headache in which only 10 cases out of 232 (4.3%) patients were positive (p<0.05). Cases referred from neurosurgery department and emergency yielded more positive results as compared to case referred from other outpatient departments. Journal of Chitwan Medical College 2013; 3(4); 9-12 DOI: http://dx.doi.org/10.3126/jcmc.v3i4.9546